Transformasi Karakter Guru Sebagai Hamba Yang Melayani Berdasarkan Injil Yohanes 13:1-38 - Kasse, Yublina (STT Pelita Dunia, 2024)
Jesus as a genealogical model of the character of the teacher as a servant who serves has the aim of exploring the transformation of the character of the teacher as a servant who serves, by emulating Jesus Christ based on John 13:1-38. Jesus is an example of a serving character that provides a framework for teacher to internalize the values of service that reflect the character of humility, character, love, character of serving and giving examples and devation in the learning and teaching prochess, The method in the study used a descriptive qualitative approach, by analyzing how the principles of Jesus’ service can be applied in the context of Christian education. The results of the quality of teaching, but also shape the character of better students. It is councluded that Christian religious education teachers who serve with a sincere and humbale heart are able to be inspiring role models for students, can enoucourage students, to develop strong moral and spiritual values and emphasie the importance of integrity and exemplary behavior.